Assessment of Arterial Stiffness Using the Cardio-Ankle Vascular Index – What We Know and What We Strive for - A. N. Sumin; A. V. Shcheglova (Рациональная фармакотерапия в кардиологии)
Currently, the importance of assessing arterial stiffness as an integral indicator of cardiovascular risk, an indicator of arteriosclerosis, and a predictor of cardiovascular events has been demonstrated. The traditional indicator of arterial stiffness-pulse wave velocity-depends on the level of blood pressure, which makes it difficult to use it for dynamic assessment. The proposed new arterial stiffness index-the cardio-ankle vascular index (CAVI), does not depend on the level of blood pressure and is more convenient in practical use. CAVI has been widely used in clinical medicine for the past 15 years as an index for assessing cardiovascular diseases and risk factors, which has allowed for the expansion and deepening of research on this topic. This review focuses primarily on recent publications and new opportunities for evaluating vascular function using CAVI. The review provides information on solving methodological problems in evaluating CAVI, highlights the relationship between CAVI and future cardiovascular events, and provides cross-sectional data on the Association of CAVI with the presence of cardiovascular diseases and their risk factors. The results of studies on the effect of drug therapy and measures to control risk factors for cardiovascular diseases on CAVI are presented. While it remains unclear how much changes in CAVI over time can affect the forecast, research is currently being conducted in this direction. The use of CAVI also opens up new perspectives in the assessment of cardiovascular interactions, the study of vascular function in vasculitis and vascular injuries, as well as in geriatric medicine (concepts of premature vascular aging and excess vascular aging).